Insomnia, nightmares, and chronotype as markers of risk for severe mental illness: Results from a student population. - Sheaves, B; Porcheret, K; Tsanas, A; Espie, C; Foster, R; Freeman, D; Harrison, P; Wulff, K; Goodwin, G (American Academy of Sleep Medicine, 2016)
Study Objectives To group participants according to markers of risk for severe mental illness based on subsyndromal symptoms reported in early adulthood and evaluate attributes of sleep across these risk categories. Methods An online survey of sleep and psychiatric symptomatology (The Oxford Sleep Survey) was administered to students at one United Kingdom university. 1403 students (undergraduate and postgraduate) completed the survey. The median age was 21 (interquartile range = 20–23) and 55.60% were female. The cross-sectional data were used to cluster participants based on dimensional measures of psychiatric symptoms (hallucinations, paranoia, depression, anxiety, and (hypo)mania). High, medium, and low symptom groups were compared across sleep parameters: insomnia symptoms, nightmares, chronotype, and social jet lag. Results Insomnia symptoms, nightmares frequency, and nightmare-related distress increased in a dose-response manner with higher reported subsyndromal psychiatric symptoms (low, medium, and high). The high-risk group exhibited a later chronotype (mid sleep point for free days) than the medium- or low-risk group. The majority of participants (71.7%) in the high-risk group screened positive for insomnia and the median nightmare frequency was two per 14 days (moderately severe pathology). Conclusions Insomnia, nightmares, and circadian phase delay are associated with increased subsyndromal psychiatric symptoms in young people. Each is a treatable sleep disorder and might be a target for early intervention to modify the subsequent progression of psychiatric disorder.